Oberflächenausbildung und tribologische Eigenschaften excimerlaserstrahlbearbeiteter Hochleistungskeramiken - Becker, Wolfgang (Friedrich-Alexander-Universität Erlangen-Nürnberg, 1999)
Excimer laser processing offers new possibilities for the surface finishing of ceramics which exceed and/or complete the variety of conventional finishing methods. In order to optimize the surface topography of ceramics for lubricated sliding applications, two different ways of surface treatment by excimer laser radiation are examined: One is the homogeneous modification of the surface topography, i.e. reducing or increasing the roughness or waviness of the ceramics depending on the laser processing parameters. The other possibility is the microstructuring of the surface by a mask projection technique. The surface structures act as lubricant pockets and generate hydrodynamic pressures in the lubricant at high sliding velocities and thus support a full lubricant-film separation of the contact bodies of the bearing. The experimental results indicate that the load-carrying capacity of ceramic bearings is improved both by a homogeneous modification of the surface topography and by the microstructuring of the surface. A significant increase of the lubricant film thickness can be achieved for both examined alternatives. The regime of elastohydrodynamic lubrication could possibly be extended to lower sliding velocities; this could minimize wear-intensive boundary lubrication at frequent starting and running-out procedure